Study on Adsorption Properties of Modified Corn Cob Activated Carbon for Mercury Ion - Yuyingnan Liu; Xinrui Xu; Bin Qu; Xiaofeng Liu; Weiming Yi; Hongqiong Zhang (Energies, 2021)
In this study, corn cob was used as raw material and modified methods employing KOH and KMnO4 were used to prepare activated carbon with high adsorption capacity for mercury ions. Experiments on the effects of different influencing factors on the adsorption of mercury ions were undertaken. The results showed that when modified with KOH, the optimal adsorption time was 120 min, the optimum pH was 4; when modified with KMnO4, the optimal adsorption time was 60 min, the optimal pH was 3, and the optimal amount of adsorbent and the initial concentration were both 0.40 g/L and 100 mg/L under both modified conditions. The adsorption process conforms to the pseudo-second-order kinetic model and Langmuir model. Scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM-EDS), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and Zeta potential characterization results showed that the adsorption process is mainly physical adsorption, surface complexation and ion exchange.